IDENTIFIKASI SISTEM DENGAN METODE WAKTU-KONTINU DAN APLIKASINYA PADA PLANT TURBOGENERATO - Rindi, Welly
Existing methods to determine a continuous-time model from sampled data usually classified into two broad categories: direct and indirect methods. In practice, the second method used commonly with the conventional system identification techniques. Contrary, the objective of this research is to describe a technique for identification multi-input and multi-output system (MIMO system) measurement data using the direct method. In the manner of this method, the approach to describe the signals between the sampling instants is to make judicious use of piecewise constant excitation signals (ZOH-assumption) and GPMF (Generalised-Poisson-Moment-Functional) when subjected to the samples of input-output measurement data. The system identification algorithm constructed and implemented by using MATLAB 6.5 System Identification Toolbox. The continuous-time system identification algorithms that have developed, applied to identify simulation model system and the turbogenerator pilot plant. Both of them consist of two inputs and two outputs. The result shows that the algorithms able to modelling the system dynamics characteristic such represented in state-space equations and the transfer function forms with the significantly coefficient of determination values. Coefficient of determination is the ratio of simulation output result and the real measurement output data. For simulation model, the coefficient of determination at output I were 99.0 % and at the output II were 99.01 %. For turbogenerator plant at the first operating point, the coefficient of determination for each of the output (output I and output II) were 81.1 % and 90.5 %, meanwhile, for the second operating point were 92.5 % and 89.1